PENGARUH PENDEKATAN TARI PENDIDIKAN DALAM MENINGKATKAN KEMAMPUAN MENDEMONSTRASIKAN MOTIF GERAK DASAR PADA SISWA DOWN SYNDROME - Khotimah, Rizky Nurul; Jaeni; Fussalam, Yahfenel Evi (Jurnal Citra Pendidikan, 2026)
This research was about the difficulty faced by down syndrome’s students. They are students who have a mental disorder and have below average level of intelligence, difficult to adapt in around environment and have disorder of their motoric or movement, they have disorder of their weak’s muscle and disorder of their balance. The effect for that is down syndrome’s students is difficult to walk, run, jumping, etc. Specifically, down syndrome’s students is very week in psychomor aspects to design a movement. So, in improved their motoric’s ability it was needed a method or the right approachment to make in learned of art dance could developt well. To solved this problem, it was required on approachment, it was approachment educational dance. This research conducted to known, is the learning of basic motions had influence of developed on down syndrome’s students motoric in SLB C Purnama Asih Bandung. Research methodology used Single Subject Research (SSR) with design A-B-A research. Data collection technique was by behavior test and data analysis technique used percentage. The result of research obtained mean level process on baseline phase 1 (A-1), in amount of 42.5%. Result of mean level of intervention phase (B) in amount of 70.8% and baseline phase 2 (A-2) was 100%. The result of this research stated that by learned of basic movement motif for dance art could improved motoric ability and improved adaption in around environment of down syndrome’s students. It was proved from the increased of mean level in every session, so the learned of basic movement used educational dance approachmnet was significant enough and it didn’t happen any overlap, in increased motoric ability and the adaptation in aroud environment. Keyword : Down Syndrome, Educatinal Dance Approachment, Motoric.